Rapid and cost-effective antenatal diagnosis of haemoglobin Bart's hydrops foetalis syndrome using a duplex-polymerase chain reaction - Wee, Yong Chui; Tan, Kim Lian; Tan, Peng Chiong; Yap, S.F. (Malaysian Medical Association, 2005)
Haemoglobin Bart's hydrops foetalis syndrome (--SEA/--SEA) is not compatible with life and contributes to a majority of the hydropic foetuses in the Malaysian Chinese alpha-thalassaemia carriers who possess the 2-alpha-gene deletion in cis (--SEA/alphaalpha). A duplex-PCR which simultaneously amplifies a normal 136 bp sequence between the psialpha-alpha2-globin genes and a 730 bp Southeast Asian deletion-specific sequence (--SEA) between the psialpha2-theta1-globin genes was established. The duplex-PCR which detects the --SEA deletion in both chromosomes serves as a rapid and cost-effective confirmatory test in the antenatal diagnosis of Haemoglobin Bart's hydrops foetalis syndrome in Malaysia. In addition, the duplex-PCR is simple to perform as both the normal and deletion-specific alpha-globin gene sequences are amplified in the same PCR reaction.